Several Proinflammatory Genes' Variability and Phenotypes of Atopic Dermatitis in Czech Adult AD Patients - Vašků, Vladimír; Vašků, Anna (Genes, 2025)
BACKGROUND: The etiopathogenesis of atopic dermatitis is complicated, and it includes aspects such as dysfunction of the skin barrier, changes in immune responses, IgE-mediated hypersensitivity, and many characteristics of the environment. Regarding skin barrier dysfunction, a number of genetic changes have been described. This genetic predisposition could be related to the phenotypes of atopic dermatitis. AIM: In this study, several polymorphisms in five proinflammatory genes were associated with certain phenotypes of AD patients (genotype-phenotype study). METHODS: In total, 89 unrelated AD Czech (Caucasian) patients were genotyped regarding five proinflammatory gene polymorphisms (angiotensinogen AGT M235T, AGT-6 G/A, TNF-α-238 G/A, TNF-β Fok1, IL-6-174 C/G and IL-6-596 G/A). Genotyping was performed using PCR and restriction analysis. For phenotypes, patients' sex, age and personal and family history of atopy, aero- and food allergies and other complex diseases were evaluated. RESULTS: A significant association with transepidermal water loss (TEWL) measured on the forearm was found with the AGT M235T polymorphism (p = 0.02). For the AG genotype of TNF-α-238 G/A, a six-times higher risk for a family history of diabetes mellitus compared to other examined aspects of family history was found (p = 0.02). A family history of thyreopathy was associated with the IL-6-174 G/C polymorphism when compared to a family history of other complex diseases. The GG genotype had a ten-times higher risk for a family history of thyreopathy compared to the other genotypes (p = 0.004). This result was highly specific (0.914). The GG genotype of IL-6-596 G/A was associated with a family history of thyreopathy, with the same result (p = 0.004). Moreover, the G allele of IL-6-174 G/C was associated with a family history of thyreopathy compared to AD patients without a positive family history of complex diseases (p = 0.03). In AD men, the MM genotype of the AGT M235T gene was found to be associated with food allergies (p = 0.004). This result was highly sensitive (0.833). A family history of cardiovascular disease in AD men was associated with AGT-6 G/A variability. The A allele was found to be six times more frequent in patients with a positive family history of cardiovascular disease (p = 0.02, with high sensitivity and specificity (0.700 and 0.735, respectively)). A family history of diabetes mellitus was associated with the TNF-β Fok1 polymorphism, where the B1 allele was almost six times more frequent in AD men with a positive family history of diabetes mellitus (p = 0.02), with high sensitivity (0.85). A significant association between TEWL measured on the forearm and the AGT M235T polymorphism was found when AD women were carriers of the MM genotype, with a median of 25 and range 4-61; those patients with the MT genotype had a median of 10 and range of 0.3-39; and patients with the TT genotype had a median of 5 and range of 3-40, p = 0.003. The polymorphism AGT-6 G/A was associated with different ages of eczema onset. The AG genotype was almost nine times more risky for the youngest group (0-7 years) compared to the oldest group (more than 18 years) (p = 0.02), with high specificity for this result. CONCLUSIONS: Our results in the field of cytokine signaling in the immune system in patients with atopic dermatitis are in agreement with those of GWASs. We suggest that cost-effective and simple PCR tests may be the best approach for the rapid and optimal collection of valid genetic information in clinical practice.
Keywords: phenotype; lidé středního věku; Czech Republic; Polymorphism, Single Nucleotide; Genotype; genetická predispozice k nemoci; Female; mladý dospělý; Dermatitis, Atopic; Humans; dospělí; atopic dermatitis; Male; fenotyp; ženské pohlaví; Middle Aged; Genetic Predisposition to Disease; Young Adult; jednonukleotidový polymorfismus; Česká republika; marker; lidé; Tumor Necrosis Factor-alpha; atopická dermatitida; interleukin-6; Phenotype; mužské pohlaví; TNF-alfa; genotyp; genetics; Interleukin-6; Adult; family history